Genetic variation is associated with PTSD risk and aversive memory: Evidence from two trauma-Exposed African samples and one healthy European sample. Issue 1 (December 2018) - Wilker, Sarah; Schneider, Anna; Conrad, Daniela; Pfeiffer, Anett; Boeck, Christina; Lingenfelder, Birke; Freytag, Virginie; Vukojevic, Vanja; Vogler, Christian; Milnik, Annette; Papassotiropoulos, Andreas; Quervain, Dominique; et al.
Abstract The probability to develop posttraumatic stress disorder (PTSD), characterized by vivid, intrusive emotional memories of the encountered traumatic events, depends - among other factors - on the number of previous traumatic experiences (traumatic load) and individual genetic vulnerability. So far, our knowledge regarding the biological underpinnings of PTSD is relatively sparse. Genome-wide association studies (GWAS) followed by independent replication might help to discover novel, so far unknown biological mechanisms associated with the development of traumatic memories. Here, a GWAS was conducted inN = 924 Northern Ugandan rebel war survivors and identified seven suggestively significant single nucleotide polymorphisms (SNPs;p ≤ 1 × 10−5 ) for lifetime PTSD risk. Of these seven SNPs, the association of rs3852144 on chromosome 5 was replicated in an independent sample of Rwandan genocide survivors (N = 370, p < .01). While PTSD risk increased with accumulating traumatic experiences, the vulnerability was reduced in carriers of the minor G-allele in an additive manner. Correspondingly, memory for aversive pictures decreased with higher number of the minor G-allele in a sample ofN = 2698 healthy Swiss individuals. Finally, investigations onN = 90 PTSD patients treated with Narrative Exposure Therapy indicated an additive effect of genotype on PTSD symptom change from pre-treatment to four months after treatment, but not between pre-treatment and the 10-months follow-up. In conclusion, emotional memory formation seems to decline with increasing number of rs3852144 G-alleles, rendering individuals more resilient to PTSD development. However, the impact on therapy outcome remains preliminary and further research is needed to determine how this intronic marker may affect memory processes in detail.